Diversity of Phytochemical and Antioxidant Characteristics of Black Mulberry (Morus nigra L.) Fruits from Turkey - Sona Skrovankova; Sezai Ercisli; Gursel Ozkan; Gulce Ilhan; Halil Ibrahim Sagbas; Neva Karatas; Tunde Jurikova; Jiri Mlcek (Antioxidants, 2022)
Black mulberry (Morus nigra L.) fruits are known due to their delicious, sweet and slightly acid flavor and high anthocyanin content. In the present study, the diversity of phytochemical, sensory, and antioxidant characteristics of the fruits of 20 black mulberry genotypes, from the Artvin region of Turkey, were evaluated. As important phytochemical assessments in fruits, we chromatographically (HPLC/DAD) determined glucose (7.22 to 11.10 g/100 g fresh weight (fw)) and fructose content (6.32 and 9.94 g/100 g fw), as well as predominant organic acid in black mulberry genotypes fruits—malic acid (6.02–11.44 g/100 g fw), followed by citric acid. Titrative determination was used for ascorbic acid, finding contents of 17.41–28.33 mg/100 g fw. There was found a great diversity of sensory (taste, juiciness, and aroma) characteristics, indicating a richness of the fruit germplasm. Antioxidant parameters, such as total phenolic (TP) and anthocyanin (TA) content, were assessed spectrometrically; antioxidant activity (AA) was assessed by DPPH and FRAP assays; individual flavonoids and phenolic acids were determined chromatographically (HPLC/DAD). Antioxidant characteristics of the fruits, defined by TP and TA content, ranged from 1951 to 2733 μg GAE/g fw and 508–712 μg C3GE/g fw, respectively. The most abundant compounds of flavonoids and phenolic acids groups were determined to be rutin (47.10–97.20 mg/100 g fw) and chlorogenic acid (51.3–90.8 mg/100 g fw). AA results, measured by the DPPH method as EC50 value, ranged between 16.10 and 25.45 μg/mL; a FRAP assay revealed values of AA between 9.80 and 13.22 μmol TE/g fw. Significant differences in phytochemical and antioxidant qualities were observed among the analyzed M. nigra genotypes. Regarding the best values of phytochemical and antioxidant characteristics, three genotypes of M. nigra were selected to be recommended for fruit production. The results thus highlight the potential for the exploitation of local black mulberry genotypes through crop selection and breeding program.